The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1080/01460860490279545
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' Perspectives on the Treatment for Pediatric Hematology: Extending the Findings

Abstract: There is scant research available about how fathers cope with their children receiving difficult treatment protocols for diseases such as childhood acute lymphoblastic leukemia (ALL). The present discussion contributes to this area with findings on the paternal experience of treatment for pediatric ALL collected from the families in a longitudinal study conducted at Royal Children's Hospital and the Mater Children's Hospital, Brisbane, Queensland. These findings emphasize the emotional shock and pain fathers e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(69 citation statements)
references
References 24 publications
(26 reference statements)
0
66
0
3
Order By: Relevance
“…The final sample consisted of 16 studies (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) . As shown in Chart 1, the articles were published between 2001 and 2013 in six different countries: Australia (N=4), the United States (N=4), Canada (N=4), Brazil (N=2), China (N=1) and Ireland (N=1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final sample consisted of 16 studies (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) . As shown in Chart 1, the articles were published between 2001 and 2013 in six different countries: Australia (N=4), the United States (N=4), Canada (N=4), Brazil (N=2), China (N=1) and Ireland (N=1).…”
Section: Resultsmentioning
confidence: 99%
“…Was the recruitment strategy appropriate to the aims of the research? 2 (27)(28)(29)(30)(31)(32) 10 (21,23,(25)(26)(29)(30)(31)(32)(33)(34) 4 (24,(27)(28)36) 5. Was the data collected in a way that addressed the research issue?…”
Section: Wills 2009mentioning
confidence: 99%
See 2 more Smart Citations
“…These few investigations have focused predominantly on the impact of cancer on parents whose offspring have cancer (Goldbeck, 2001;McGrath & Chesler, 2004), the impact of parental cancer on children and adolescents (Harris & Zakowsky, 2003;Lewis, Hammond, & Woods, 1992;Osborn, 2007), and overwhelmingly on spouses of cancer patients (Case, 2004 For example, Welch, Wadsworth, and Compass (1996) examined the impact of a parental cancer diagnosis on children and adolescents. The authors found that while parents did not perceive any distress in their children (6 to 10 year olds) and adolescents (11-18 year olds) following the diagnosis, adolescents and children scored high in anxiety/depression and aggression measures.…”
Section: Impact Of Cancer In the Familymentioning
confidence: 99%